Swollen legs and false nephrotic syndrome: a case of primary lymphatic dysplasia with intermittent chyluria - Giorgia Sasia; Teresa Morgillo; Christian Bracco; Corrado Magnino; Giulia Racca; Remo Melchio; Luigi Maria Fenoglio (European Journal of Case Reports in Internal Medicine)
Chyluria, defined as the presence of chyle in urine, is a rare condition caused by an abnormal communication between the lymphatic system and the urinary tract. It can present with massive proteinuria and characteristic milky urine, mimicking nephrotic syndrome. We report the case of a 23-year-old woman with a history of seronegative ocular myasthenia gravis who developed progressive bilateral lower extremity oedema and intermittent nephrotic-range proteinuria despite normal serum albumin and lipid profiles. A renal biopsy, performed to investigate proteinuria, was complicated by a subcapsular hematoma. Shortly thereafter, the patient developed dysuria, urinary retention, and milky urine, leading to the diagnosis of chyluria. Imaging revealed thrombosis of the left iliac vein, associated with hereditary thrombophilia (heterozygosity for factor V Leiden and homozygous G20210A prothrombin mutation), prompting anticoagulation therapy. Lymphoscintigraphy suggested a lympho-vesical fistula and bilateral inguinal lymph node dysplasia. Conservative management, including urinary catheterization, fluid optimization, and dietary modifications with a low-fat, medium-chain triglyceride-enriched regimen, resulted in resolution of chyluria. At 6-month follow-up, there was no recurrence of symptoms, proteinuria improved, and anticoagulation was continued. This case highlights the importance of a multidisciplinary approach in managing rare presentations of chyluria, nephrotic proteinuria, and venous thrombosis.